Identifying Research Frontiers In Dynamic Pricing Capability And Revenue Optimization Using Bibliometric Science Mapping Techniques - La Ode Sugianto; Dwi Warni Wahyuningsih; Siti Chamidah; Wa Ode Sitti Nurrhamah; La Harjono (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to identify the knowledge structure, patterns of scientific collaboration, the evolution of research themes, and research frontiers in the study of Dynamic Pricing Capability (DPC) and Revenue Optimization (RO) during the period 2020-2025. The study uses a quantitative-descriptive bibliometric approach with data sources derived from the Dimensions database using the keywords